Kepastian Hukum Kepemilikan Tanah dan Bangunan Bagi Pembeli Perumahan Korpri Griya Mutiara Indah di Penajam Paser Utara - Ismi Dayana; Purwanto; Aryo Subroto (Jurnal Risalah Hukum, 2023)
One of the forms of transfer of regional property is through a grant with the approval of the regent. However, civil servants as recipients of land grants in 2008 and 2014 have not been able to issue them as Certificates of Ownership. This study aims to identify the inhibiting factors for the issuance of Property Rights Certificates, as well as to analyze legal certainty regarding land and building ownership for buyers and to find out the forms of efforts that can be taken by grantees. This study produces and proposes the following findings: First, the inhibiting factors in the issuance of certificates of property rights at the Korpri Griya Mutiara Indah housing estate in North Penajam Paser are the legal substance factor and the legal factor. second, the legal certainty of land and building ownership for the buyer in the form of Building Use Rights on the land of Management Rights which is still a regional asset and the efforts that can be made by the recipient of the land grant for the Korpri Griya Mutiara Indah Housing in North Penajam Paser can be done first. through the Regional Finance and Assets Agency, which then develops regional property in the form of land with management rights, approval from the DPRD is needed so that civil servants can apply for an upgrade to a Certificate of Ownership to the land office of North Penajam Paser Regency.